2017
DOI: 10.1021/acs.nanolett.7b03312
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Driven Unidirectional Optical Nanoantennas

Abstract: Directional antennas revolutionized modern day telecommunication by enabling precise beaming of radio and microwave signals with minimal loss of energy. Similarly, directional optical nanoantennas are expected to pave the way toward on-chip wireless communication and information processing. Currently, on-chip integration of such antennas is hampered by their multielement design or the requirement of complicated excitation schemes. Here, we experimentally demonstrate electrical driving of in-plane tunneling nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 38 publications
2
67
0
Order By: Relevance
“…With the years, researchers have first learnt to mitigate the wearout problem, and later on to master it. As of today, some degree of control of this inherently stochastic phenomenon has been achieved, permitting to create nanogaps for addressing nanoclusters or single molecules [2][3][4], locally modify the geometry or the material properties to fabricate point contacts [5][6][7], superconducting weak links [8][9][10], nanoheaters [11], plasmonic nanoantennas [12], etc. In addition, recent works also showed that the change of electrical resistance in random networks of conducting nanowires under electric bias can induce percolation in these materials, making them interesting transparent conducting materials suitable in a wide range of applications, as window electrodes, transparent heaters, antennas, etc [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…With the years, researchers have first learnt to mitigate the wearout problem, and later on to master it. As of today, some degree of control of this inherently stochastic phenomenon has been achieved, permitting to create nanogaps for addressing nanoclusters or single molecules [2][3][4], locally modify the geometry or the material properties to fabricate point contacts [5][6][7], superconducting weak links [8][9][10], nanoheaters [11], plasmonic nanoantennas [12], etc. In addition, recent works also showed that the change of electrical resistance in random networks of conducting nanowires under electric bias can induce percolation in these materials, making them interesting transparent conducting materials suitable in a wide range of applications, as window electrodes, transparent heaters, antennas, etc [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Another optical functionality that is in the focus of the plasmonics community is the directional routing of light. Not only individual nanostructures were demonstrated for directional scattering of far-field light [11][12][13], color-routing [14], quantum emitter radiation steering [9,[15][16][17][18][19], electro-luminescence [20,21] or directional non-linear emission [22]. Also metasurfaces for directional scattering and color-routing have been proposed [23,24].…”
mentioning
confidence: 99%
“…Directional emission of an optical antenna driven by IET was achieved by Gurunarayanan et al with the design illustrated in Fig. 7(a) [134] . It consists of two electrically connected rod antennas that are aligned edge to edge at an angle of 90 • .…”
Section: Emission Control Via Antenna Designmentioning
confidence: 99%